2016
DOI: 10.1002/ece3.2585
|View full text |Cite
|
Sign up to set email alerts
|

Wind estimation based on thermal soaring of birds

Abstract: The flight performance of birds is strongly affected by the dynamic state of the atmosphere at the birds' locations. Studies of flight and its impact on the movement ecology of birds must consider the wind to help us understand aerodynamics and bird flight strategies. Here, we introduce a systematic approach to evaluate wind speed and direction from the high‐frequency GPS recordings from bird‐borne tags during thermalling flight. Our method assumes that a fixed horizontal mean wind speed during a short (18 sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…As first proposed by Weinzierl et al. () in the field of atmospheric simulation, our study suggests animals are useful sensors and we showed they can also provide valuable ground‐truth data for remote sensing‐based land cover classification. We mapped agricultural land over three test regions (R1, R2, R3) based on White Stork movement data and achieved high accuracies in R1 and R3.…”
Section: Discussionsupporting
confidence: 71%
“…As first proposed by Weinzierl et al. () in the field of atmospheric simulation, our study suggests animals are useful sensors and we showed they can also provide valuable ground‐truth data for remote sensing‐based land cover classification. We mapped agricultural land over three test regions (R1, R2, R3) based on White Stork movement data and achieved high accuracies in R1 and R3.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have measured turn radius using GPS corrected for wind drift (e.g. Weinzierl et al, 2016;Treep et al, 2016). By using the airspeed, we can derive radius from the reference frame of the bird, removing the effect of drift on its path.…”
Section: Derivation Of Soaring Parametersmentioning
confidence: 99%
“…Few studies have quantified bank angle directly, although some in-flight angular measurements have previously been recorded incidentally using on-board cameras, for example, to quantify the lateral displacement of the tail in the flight manoeuvres of a steppe eagle, Aquila nipalensis (Gillies et al, 2011). Turning radii can also be derived using GPS data (adjusted for wind drift) or measures of airspeed (Treep et al, 2016;Weinzierl et al, 2016;Horvitz et al, 2014;Sherub et al, 2016). However, deriving bank angle from these measures of turn radius assumes that birds adopt the angles that are required for theoretically ideal circling flight (cf.…”
Section: Introductionmentioning
confidence: 99%
“…This research adds to the growing body of work that uses onboard data loggers to test the underlying theory of soaring flight (Shepard, Ross, & Portugal, 2016;Sherub et al, 2016;Treep et al, 2016;Weinzierl et al, 2016). In addition to understanding the costs and benefits of inhabiting contrasting energy landscapes, improved knowledge of flight behaviors can be used for modeling potential anthropogenic risks, in particular the effects of wind turbines and associated energy infrastructure (McLeod, Whitfield, & McGrady, 2002;Reid et al, 2015).…”
Section: Discussionmentioning
confidence: 99%